2014
DOI: 10.4155/fmc.14.65
|View full text |Cite
|
Sign up to set email alerts
|

The Discovery of Medicines for Rare Diseases

Abstract: There is a pressing need for new medicines (new molecular entities; NMEs) for rare diseases as few of the 6800 rare diseases (according to the NIH) have approved treatments. Drug discovery strategies for the 102 orphan NMEs approved by the US FDA between 1999 and 2012 were analyzed to learn from past success: 46 NMEs were first in class; 51 were followers; and five were imaging agents. First-in-class medicines were discovered with phenotypic assays (15), target-based approaches (12) and biologic strategies (18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…Analysis of a decade of drug approvals showed that the majority of first‐in‐class medicines were discovered with approaches (phenotypic) that did not require an exact understanding of the target or MMOA, whereas this knowledge contributed to the success of follow‐up drugs in which the mechanism was previously identified . In a separate analysis of approvals of medicines for rare diseases, it was concluded that genetic contributions (25%) were underrepresented with respect to the number of genetic diseases (>80%) . Successful genetic approaches, whereas being fewer than expected based on the number of genetic diseases, were in disease areas with supporting knowledge to facilitate the discovery (e.g., kinases for cancer, enzyme replacement therapy for inborn error of metabolism, and areas in which sufficient knowledge of physiology identified therapeutic opportunities) …”
Section: Why Is the Productivity And Success Low?mentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of a decade of drug approvals showed that the majority of first‐in‐class medicines were discovered with approaches (phenotypic) that did not require an exact understanding of the target or MMOA, whereas this knowledge contributed to the success of follow‐up drugs in which the mechanism was previously identified . In a separate analysis of approvals of medicines for rare diseases, it was concluded that genetic contributions (25%) were underrepresented with respect to the number of genetic diseases (>80%) . Successful genetic approaches, whereas being fewer than expected based on the number of genetic diseases, were in disease areas with supporting knowledge to facilitate the discovery (e.g., kinases for cancer, enzyme replacement therapy for inborn error of metabolism, and areas in which sufficient knowledge of physiology identified therapeutic opportunities) …”
Section: Why Is the Productivity And Success Low?mentioning
confidence: 99%
“…The C1‐esterase‐inhibitor is an inhibitor of plasma kallkrein and regulates the activation of complement and intrinsic coagulation. Kalbitor works by inhibition of the conversion of HMW kininogen to bradykinin and icatibant is a competitive antagonist selective for the bradykinin B2 receptor . Knowledge of the genetic and biochemical pathways facilitated the identification of these treatments.…”
Section: Why Is the Productivity And Success Low?mentioning
confidence: 99%
See 1 more Smart Citation
“…They are also generally characterized by there being over 7000 of them, with only a few hundred having treatments and in some cases these can be incredibly expensive (1). The families affected by these rare diseases are also in most cases highly motivated to raise funds and reach out to researchers and pharma and biotech companies (2).…”
Section: Introductionmentioning
confidence: 99%
“…There are over 7000 rare diseases, approximately 75% affect children and over 340 currently have treatments. Research for rare diseases has therefore been termed an example of a long-tailed problem 1 in which traditional research has focused on the 20% of genetic conditions (accounting for 80% of all diseases), but at the same time neglecting the other 80% of genetic conditions representing the remaining 20% of all diseases (rare diseases) 2, 3 . The irony here is that rare diseases can in general be readily treated by replacing the gene, protein or stabilizing protein folding etc.…”
mentioning
confidence: 99%